Hyperbranched polysiloxane functionalized graphene oxide for dicyclopentadiene bisphenol dicyanate ester nanocomposites with high performance - H. X. Yan; M. M. Zhang; C. Gong; T. T. Li (eXPRESS Polymer Letters, 2014)
We report an efficient and novel method to functionalize graphene oxide (GO) with hyperbranched polysiloxane and successfully compound them with dicyclopentadiene bisphenol dicyanate ester (DCPDCE) to prepare nanocomposites. X-ray photoelectron spectroscopy (XPS) and Fourier-transform infrared spectra (FT-IR) were employed to examine the surface functionalization of GO. The effects of functionalized GO on the curing reaction, mechanical, dielectric and thermal properties of DCPDCE resin were investigated systematically. Results of DSC show that the addition of modified GO can facilitate the curing reaction of DCPDCE and decrease the curing temperature of DCPDCE. Compared with pure DCPDCE resin, the impact and flexural strengths of the nanocomposite materials are improved markedly with up to 66 and 50% increasing magnitude, respectively. Meanwhile, the modified GO/DCPDCE systems exhibit lower dielectric constant and loss than pure DCPDCE resin over the testing frequency from 10 to 60 MHz. In addition, the thermal stability and moisture resistance of modified GO/DCPDCE nanocomposties are also superior to that of pure DCPDCE resin.